Gênero, educação profissional e subjetivação - Santos, Elza Ferreira (2013)
This research was based on the idea that new professional configurations have come due to some women are pursuing careers once considered to be male ones, and it progressed in order to understand how those new configurations of female subjectivity are being built, the way women are positioning themselves on the working market, and also the way gender relations develop themselves as far as women and men are together in the classroom, their conquest of traineeship and how male and female careers are received by contemporary society. We are based on the studies of gender inserted into a post-structuralist perspective, particularly those who advocate the need to escape from sociocultural apparatus that leads men and women to a male and female binarism. Thus, gender is understood as a performance, resulting from historical contingencies, so, it is not considered as a fixed and immutable identity. Men and women are in a network of power, confronting several interests, sometimes contradictory. They produce speeches and use them to express their choices and questions, their body and subjectivity. In speeches, there are strategies and resistances used in the daily school environment and in the world of work. The research is located at Educator Training: Knowledge and Skills line which belongs to the Center for Graduate Education at the Federal University of Sergipe. A special emphasis was given to theorists from the areas of education, gender, labor and technology. Our categories (gender - professional education and work - subjectivity) were built from what was learned in the relationship between theoretical and empirical body of research. The categories focused on the symbolic universe of discourse in our society and were analyzed through Foucaultian bias. The research subjects were students of integrated and subsequent courses of Electrotechnics, Electronics, Systems Development, Chemistry and Work Safety at the Federal Institute of Sergipe. For a year long, we conducted five focal groups with current and former male and female students besides six interviews with current and former female students. These strategies were inserted in a qualitative approach, which has not prevented us from elaborating a lot of graphics that show disparities, as well as advances and setbacks, with regard to the registration of male and female students who take part to subsequent and integrated courses, particularly the ones involved in our research. Finally, the thesis shows that the processes of subjectivity are frequent, dynamic and controversial, do not happen from time to time but accordingly to the story each one carries out. The school gear is usually challenged by new anxieties experienced from the dynamics of the classroom, corridors, laboratories and from some other anxieties brought by the experiences with family and the world of work. That's the instrument for the construction of subjectivity and the composition of new gender relations in the student body at the Federal Institute of Sergipe